2003
DOI: 10.1007/bf03166932
|View full text |Cite
|
Sign up to set email alerts
|

ESR study of rare-earth ions with the effective spin of 1/2 in LiNbO3 crystals

Abstract: Rare-earth ions of Nd 3 § and Er 3 § in nearly stoichiometric and MgO-doped LiNbO 3 crystals, respectively, have been investigated by employing an X-band electron spin resonance (ESR) spectrometer. The grown crystal was heated in Li-rich powder at ll00~ in order to make it nearly stoichiometric by the vapor transport equilibrium technique. Due to the fact that the ESR linewidth is much narrower in the stoichiometric crystal than in the congruent LiNbO3, we were able to determine the hyperfine constants of E43N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In LiNbO 3 :Mg, Yb, Dong et al have shown that the Yb 3+ ions may occupy also Nb 5+ sites because of the role of MgO co-doping [18]. Choh et al [19] arrived at similar conclusion for Er 3+ in Er and Mg codoped LN single crystals. Malovichko and Grachev [20,21] have shown that RE ions enter octahedral sites in LN, which may exhibit the C 3 or C 1 site symmetries.…”
Section: Introductionmentioning
confidence: 69%
“…In LiNbO 3 :Mg, Yb, Dong et al have shown that the Yb 3+ ions may occupy also Nb 5+ sites because of the role of MgO co-doping [18]. Choh et al [19] arrived at similar conclusion for Er 3+ in Er and Mg codoped LN single crystals. Malovichko and Grachev [20,21] have shown that RE ions enter octahedral sites in LN, which may exhibit the C 3 or C 1 site symmetries.…”
Section: Introductionmentioning
confidence: 69%
“…The Er 3+ paramagnetic centers with axial symmetry in LiNbO 3 single crystals were investigated by many scientists [3,9,13,14]. We are focused on the Er 3+ centers in LiNbO 3 and MgO or ZnO codoped LiNbO 3 crystals because one can compare our results with those obtained by other methods in the case of this crystal.…”
Section: Erbium Centers In Lithium Niobate Crystalsmentioning
confidence: 91%
“…Choh et al [9] report SH parameters of new Nd 3+ (and Er 3+ ) centers in lithium niobate single crystal. The EPR g-factor and the local structure for the trigonal Nd 3+ center in LiNbO 3 :Nd single crys- tal are investigated, too [10].…”
Section: Neodymium Centers In Lithium Niobate Crystalsmentioning
confidence: 98%
“…the Li/Nb concentration ratio). Properties of RE 3+ centres in LN are directly related to the defects associated with the non-stoichiometric conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Rareearth (RE) dopant ions, as e.g. Nd 3+ or Er 3+ , are introduced to LN host as optically active impurities [7]. The relative concentration of such impurities depends on the stoichiometry (i.e.…”
Section: Introductionmentioning
confidence: 99%